Preemptive use of adjunctive IV lidocaine for enhanced recovery after abdominal hysterectomy for overweight and obese women: a prospective, randomized, double-blind, placebo-controlled study - Shady, Nahla Waer; Farouk, Hassan Ahmed; Sallam, Hany Farouk (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: This investigation planned to evaluate the clinical results of adjunctive IV lidocaine bolus dose plus infusion for one hour after surgery in patients who underwent an abdominal hysterectomy in obese and overweight women. Methods: We performed a double-blind, placebo-controlled study, (ClinicalTrials.gov identifier: NC03748108), with patients undergoing abdominal hysterectomy divided into 2 groups: one group received intravenous lidocaine single bolus dose preoperatively and IV infusions till one hour after the surgical procedure, and the opposite received normal saline infusion (placebo). We assessed postoperative results, including pain scores rankings on a visual analog scale (VAS) in rest and movement, administration frequency of pethidine. Postoperative nausea and vomiting, the period of hospital stay (LOS), time to ambulate, and patient satisfaction at forty-eight hours had been evaluated. Chi-square test and Monte Carlo test have been used for comparison among groups. Results: There were 120 patients in our study. The visual analog scale (VAS), pain scores, length of hospital stay (LOS), and administration frequency of pethidine were significantly lower in the lidocaine group. The total amount of consumed pethidine was significantly lower in the lidocaine than the placebo group. There was a significant reduction in post-operative pain which was assessed by visual analog scale (VAS) after 2,4,8,12, and 24 hours either during movement or during rest in the lidocaine group compared to the placebo group, p=(0. 0001,0.0001,0.0001,0.0001 and 0.0001). Conclusions: The administration of adjuvant intravenous lidocaine infusion reduces pain during the postoperative period after abdominal hysterectomy, is associated with early recovery, decreased postoperative opioid analgesic requirement, and better patient satisfaction in overweight and obese women undergoing abdominal hysterectomy.